Effects of Hydroalcoholic Extract of Matricaria Recutita L. on Lipid Peroxidation and Nitric Oxide in Pentylenetetrazole-kindled Mice: Ameliorative effects of hydroalcoholic extract of Matricaria recutita L. on epilepsy - Kazemi, Maryam; Ardjmand, Abolfazl; Esmaeil Shahaboddin, Mohammad; Mehrand, Mehdi; Banitaba-Bidgolia, Seyyed Mojtaba; Ghavipanjeh, Gholamreza (Iranian Journal of Pharmaceutical Sciences, 2021)
Matricaria recutita L. (chamomile) is a well-known medicinal plant. As the main constituents of chamomile, flavonoids such as apigenin, act on benzodiazepine/GABA receptors. This study was designed to determine the protective effect of hydroalcoholic Matricaria recutita (MR) extract (hMRxt) on pentylenetetrazole (PTZ)-induced kindling model and lipid peroxidation in mice. Forty-eight male albino mice (25-30 g) were randomly divided into six groups (n=8). Kindling was induced by 13 PTZ injections (35 mg /kg; i.p.) every other day for 26 days. The seizure score was observed and noted until 30 minutes after the PTZ injection. Finally, the mice were decapitated and their brains were dissected out so as to assess some biochemical factors, namely malondialdehyde (MDA) and nitric oxide metabolites (NOx) in the brain tissue. One-way ANOVA was used for analysis in Prism 6.0. The results showed that hMRxt (400 mg/kg) and valproate (VAP) (150 mg/kg) significantly decreased the progression and duration of seizure induced by PTZ (P <0.001). NOx level in the hMRxt (400 mg / kg), VAP (150 mg / kg) and the combination of hMRxt (50 mg / kg) + VAP (50 mg / kg) groups was significantly reduced compared to the PTZ group. Also, hMRxt (50 and 400 mg/kg) significantly increased the MDA level (P <0.001) compared to PTZ and control groups. This study revealed that hMRxt protects mice against the PTZ-induced epilepsy via NO signaling with no effect on lipid peroxidation.